2018
DOI: 10.1002/anie.201810366
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Triphenylphosphine

Abstract: Ac ompletely inorganic version of one of the most famous organophosphorus compounds,t riphenylphosphine, has been prepared. Ac omparison of the crystal structures of inorganic triphenylphosphine,P Baz 3 (where Baz = B 3 H 2 N 3 H 3 )a nd PPh 3 shows that they have superficial similarities and furthermore,t he Lewis basicities of the two compounds are remarkably similar.H owever,t heir oxygenation and hydrolysis reactions are starkly different. PBaz 3 reacts quantitatively with water to give PH 3 and with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…147 Pringle and co-workers reported the reaction between B-monochloroborazine (202) and P(SiMe 3 ) 3 (Scheme 96). 148 The product of the reaction was tris(borazin-2-yl)phos-phine (203), aptly named an inorganic analogue of triphenylphosphine.…”
Section: Review Synthesismentioning
confidence: 99%
“…147 Pringle and co-workers reported the reaction between B-monochloroborazine (202) and P(SiMe 3 ) 3 (Scheme 96). 148 The product of the reaction was tris(borazin-2-yl)phos-phine (203), aptly named an inorganic analogue of triphenylphosphine.…”
Section: Review Synthesismentioning
confidence: 99%
“…After the isolation of borazine in 1926 by Stock and Pohland, [16] it has received comparatively modest experimental attention. [17][18][19][20] After a long debate about the aromatic character of borazine, [21] electrophilic aromatic substitution of gaseous borazine was successfully carried out by Chiavarino et al which confirmed the aromatic character. Gorman et.…”
Section: Introductionmentioning
confidence: 99%
“…have synthesized borazine based inorganic analogue of triphenyl phosphine. [20] Recently, a borazine based radical cation has been experimentally characterized. [22] Bhattacharya et al have carried out theoretical investigation to understand the spin blocker capacity of borazine coupled iminonitroxide and tetrathiafulvalene-radical-cation.…”
Section: Introductionmentioning
confidence: 99%
“…due to p-donor or carborane substituents) and phosphorus thus retains its lone pair and tetrahedral geometry, are highly electron rich h 1 ligands for transition metal complexes. [9][10][11] By far the most common route for the construction of P-B bonds is salt elimination [12][13][14][15][16][17][18][19] using an alkali metal phosphide, MPR 2 , and a haloborane (Scheme 1A), although other routes are known, including nucleophilic addition of a boryl anion to a chlorophosphine (B), 20 elimination of silyl halide (C), 10,11,21 and cross-coupling of a B-I species with secondary phosphines using a palladium catalyst (D). 9 Of the different synthetic options for the construction of phosphorus-carbon bonds, hydrophosphination of unsaturated carbon substrates has gained popularity in recent years.…”
Section: Introductionmentioning
confidence: 99%